Effectiveness and authority: the Bishop of Lincoln's Court of Audience in the early sixteenth century - Roberts, Martin Owen (2020)
This thesis examines authority and effectiveness in the early sixteenth-century English ecclesiastical justice system. It concentrates upon the bishop of Lincoln’s court of audience between March 1528 and March 1530 but seeks to provide insight into that jurisdiction throughout late medieval England. To better understand how effective such justice might have been, and how some of the challenges were met, it investigates that court’s jurisdictional coverage and procedural flexibility and considers those who spent much of their working lives engaged within its arenas, their legal knowledge, acuity, professionalism, ethical outlook and inter-personal relations. It rarely deals with high politics or theology but instead with often ordinary lives and the sometimes traumatic, emotional, and uncommon events which happened to those who lived them. It looks at marriage litigation to reveal more about lay and lawyer involvement, courtroom dynamics, and decisions made by or forced upon participants whilst it was underway. It examines enforcement of discipline, especially after sexual misconduct, and particularly the processes of inquisition, sentence construction and penitential punishment. It concludes with a retrospective and looks to future research possibilities.